Pasture quality and cheese traceability index of Ragusano PDO cheese - Copani, Venera; Guarnaccia, Paolo; Biondi, Luisa; Calà Lesina, Salvatore; Longo, Stefania; Testa, Giorgio; Cosentino, Salvatore L. (Italian Journal of Agronomy, 2015)
In the Iblei plateau (Sicily, Southern Italy) the native dairy cattle breed Modicana during the spring season grazes exclusively on natural pastures for the production of the Ragusano protected denomination of origin cheese. Along the grazing season, herbage undergoes to changes on protein, fibre and moisture content, affecting quality parameters such as plant carotenoids concentration, involved in the colour and nutritional characteristics of dairy products and potential biomarkers for authenticating fed green pasture-based diets. The aim of this work was to assess whether the cheese traceability index, based on the carotenoids spectra data elaboration, could be related to seasonal variations of floral composition and pasture quality. Four herbage and cheese samples were collected every two weeks in two representative farms of this area, from March to May 2013. Pasture characteristics as pastoral vegetation composition and pastoral value were analysed using the methodology developed for pastoral resources studies. Traceability index showed a significant positive correlation with pasture moisture and crude protein content (r=0.729* and 0.853**, respectively), while it was negatively correlated with fibre content (r=–0.719*).